Factors affecting bone density in young adults - Fehily, AM; Coles, RJ; Evans, WD; Elwood, PC (The American journal of clinical nutrition, 1992)
A 14-y follow-up of 581 children who took part in a randomized controlled trial of the effect of a milk supplement on growth of children was conducted to investigate the supplement's effect on adult bone mineral content (BMC) and density (BMD). BMC and BMD of the nondominant forearm were measured by single-photon absorptiometry in 371 subjects (64%) aged 20–23 y, at a proximal site (shaft of radius and ulna) and at a distal site near the wrist. BMCs and BMDs tended to be higher in the intervention group (NS). Cross-sectionally, BMD was positively associated with body weight (P < 0.01) in both sexes; inversely associated with alcohol consumption (P < 0.05), and positively with manual occupation (NS) in men; positively associated with current intakes of calcium (P < 0.05), vitamin D (P < 0.01 ), and sports activity during adolescence (P < 0.01 ), and inversely with parity (NS) in women. In multiple linear-regression analysis body weight and sports activity during adolescence were stronger determinants of female BMD than was diet.